2016
DOI: 10.1007/s00240-016-0894-5
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxaluria-induced tubular ischemia: the effects of verapamil on the antioxidant capacity of the affected kidneys

Abstract: To evaluate the potential protective effects of a calcium channel blocker (Verapamil) on the oxidative stress related changes with an emphasis on the antioxidant capacity of the kidneys an experimental study in rats was performed. A total of 44 rats have been included. Hyperoxaluria was induced in Group 1 by continuous administration of ethylene glycol (EG). Animals in Group 2 received Verapamil in addition to EG. Animals in Group 3 constituted the control group. In addition to the evaluation of tissue and ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…As our previous research showed, the expression of antioxidants including GSH were markedly decreased in the kidney tissue in a similar rodent model of renal CaOx crystal deposition (Peng et al, ). The significantly decreased level of plasma GSH induced by CaOx in this study reflected the systemic oxidative status of the mice, according to the outcomes of another study based on a rat model (Sarica et al, ). SA capsules ameliorated the crystal‐induced oxidative stress by reversing the regulation of GSH and pyroglutamic acid.…”
Section: Discussionsupporting
confidence: 69%
“…As our previous research showed, the expression of antioxidants including GSH were markedly decreased in the kidney tissue in a similar rodent model of renal CaOx crystal deposition (Peng et al, ). The significantly decreased level of plasma GSH induced by CaOx in this study reflected the systemic oxidative status of the mice, according to the outcomes of another study based on a rat model (Sarica et al, ). SA capsules ameliorated the crystal‐induced oxidative stress by reversing the regulation of GSH and pyroglutamic acid.…”
Section: Discussionsupporting
confidence: 69%
“…Under physiological conditions, cells are equipped with numerous antioxidant systems, among others enzymatic (above discussed SOD) and non-enzymatic (GSH, vitamins E, A and C) to limit the effects of free radicals [ 44 ]. Up to a certain point, they can control the damage caused by free radicals, when this point is exceeded, cells are faced with oxidative stress, and addition of external antioxidants is necessary to maintain cell viability [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%